A Triple-Regulated Oncolytic Adenovirus Carrying MicroRNA-143 Exhibits Potent Antitumor Efficacy in Colorectal Cancer - Luo, Qifeng (Mol Ther Oncolytics, 2020)
The cancer-targeting gene virotherapy might be a useful strategy for the treatment of cancer, because it could combine the advantages of both gene therapy and virotherapy. This study aimed to construct a triple-regulated oncolytic adenovirus, Ad-RGD-Survivin-ZD55-miR-143, carrying the therapeutic gene miR-143 and evaluate its possible antitumor effect in colorectal cancer. We observed that miR-143 was lowly expressed in patients with colorectal cancer. The upregulation of miR-143 could inhibit cell proliferation and induce cell apoptosis by targeting KRAS in colorectal cancer cells. Then, Ad-RGD-Survivin-ZD55-miR-143 was successfully constructed in this study. Cells infected with Ad-RGD-Survivin-ZD55-miR-143 could inhibit cell proliferation, suppress cell migration and invasion, arrest cells at the G1 phase, and induce cellular apoptosis. At the same time, Ad-RGD-Survivin-ZD55-miR-143 decreased the expression of PARP-1 and KRAS protein in vitro. In a HCT116 xenograft model, intratumoral injection of Ad-RGD-Survivin-ZD55-miR-143 resulted in reduced tumor growth. Furthermore, Ad-RGD-Survivin-ZD55-miR-143 induced apoptosis and decreased the expression level of KRAS in HCT116 xenograft cells. Our results suggested that Ad-RGD-Survivin-ZD55-miR-143 produced a strong antitumor effect by targeting KRAS and that this strategy could broaden the therapeutic options for treating colorectal cancer.